COULD WEARING FACE MASKS DURING THE PANDEMIC HAVE CREATED AN ENVIRONMENT FOR DEMODEX MITES? - Doner Aktas , Nurhan (Sanamed, 2024)
Background: During the COVID-19 pandemic, wearing face masks became mandatory in our country to prevent the spread of the virus, as in many other countries.Objective: We aimed to examine whether wearing face masks during the pandemic created a microenvironment for Demodex mites.Material and Methods: The study included three groups: (i) those who wore N95/FFP2 masks, (ii) those who wore a 3-ply surgical mask, and (iii) a control group (who rarely wore masks). The age, gender, occupation, smoking status, alcohol consumption, past medical history, and face-washing habits were questioned, and dermatological examination was performed. The presence of Demodex mites was detected by the standard superficial skin biopsy (SSSB) from three regions of the face.Results: Sociodemographic characteristics and the findings of dermatological examination of the three groups were similar (p > 0.05). There was no significant difference across the groups concerning the presence of Demodex mites in corresponding regions (the right cheek, nose, forehead) and corresponding numbers of Demodex mites (>5 D/cm2); the total number of Demodex mites in each region; presence of Demodex mites in any area on the face, number of Demodex mites in any region >5 D/cm2 on the face, the total number of Demodex mites found on the face, and the presence of Demodex mites in the areas under the mask (the nose and the right cheek together) (p> 0.05).Conclusion: We can conclude that wearing masks by healthy adults with no known skin diseases during the pandemic does not create a proper microenvironment for the lives of Demodex mites.
Keywords: COVID-19; Demodex mites; mask